Water–Energy–Carbon Nexus Analysis for Water Supply Systems with Brackish Groundwater Sources in Arid Regions - Alresheedi, Mohammad T.; Haider, Husnain; Shafiquzzaman, Md; AlSaleem, Saleem S.; Alinizzi, Majed (Sustainability, 2022)
Limited knowledge on the water–energy–carbon nexus of water supply systems (WSSs) with brackish groundwater sources in arid regions exists to date. In addition, the large amount of fossil-fuel energy utilized by treatment processes generating a significant amount of carbon emissions remains a challenge for the municipalities in Saudi Arabia to meet long-term sustainability goals. To achieve Saudi Arabia Vision 2030’s target of sustainable cities with reduced CO2 emissions, the present study aimed to analyse the water–energy–carbon nexus for WSSs and propose mitigation measures for reducing energy and carbon footprints from both the water management and treatment technologies perspectives. The detailed energy consumption data for three main components (source extraction, water treatment, and conveyance and distribution) of the main WSS, serving the 600,000 population of Buraydah City (Qassim, Saudi Arabia), was obtained from the concerned municipality. The city water treatment plant removes naturally occurring iron, TDS, and radionuclides in the source water with the help of ion detention, oxidation, sand filtration, ultrafiltration, reverse osmosis, chlorination, and backwash water management. The study found that the treatment facility consumes around half of the total system’s energy (131,122 kWh/day); while, with deep confined aquifer (>600 m) and an average water loss of 8%, conveyance and distribution (34%) and source extraction (18%) are consistent with the reported literature. With oil-driven energy, carbon emissions were found to be 10.26, 27.18, and 19.72 million tons CO2 eq/year for source extraction, water treatment, and conveyance and distribution, respectively. The reverse osmosis process, with higher energy consumption—1.1 kWh/m3 of treated water—than the global average, consumes most (88%) of the treatment plant’s energy and thus needs effective energy management practices. Moving to renewable (solar and wind-driven) sources, subject to a detailed life cycle analysis, can achieve significant energy and associated carbon emission reductions. To sustainably meet the water demand of the growing population in arid regions, the study also suggests raising the awareness of the public about how water conservation can control CO2 emissions, proactive maintenance of aging infrastructure, and increasing rainwater and treated wastewater reuse, to enhance the operational life of existing treatment facilities.